Brain, behavior and epigenetics - Petronis, Arturas; Mill, Jonathan; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Despite significant progress in molecular epigenetic research and its enormous potential, there are still considerable challenges to overcome before we can fully understand the role of epigenetic processes in brain function and behavior. For instance, what comprises a ?normal? brain epigenome and what is the degree of region- and cellular-specificity of epigenetic landscapes in the brain? How do the multiple layers of epigenetic information interact and change over time? How common is meiotic epigenetic heritability and what role it may play in complex psychiatric disease? To what extent is the epigenome plastic and malleable in response to environmental influences? This volume demonstrates that such questions can now be explored in an experimental molecular biology laboratory. While the community is only just starting to acknowledge the importance of epigenetic processes in the brain, there is no doubt that numerous breakthrough discoveries in brain and behavioral epigenetics will be made
Preface.- 1. Post-translational histone modifications and the neurobiology of psychosis -- 2. Epigenetic regulation of GABAergic targets in psychiatry -- 3. Possible roles of DNA methylation in bipolar disorder -- 4. The epigenetics of depression and suicide -- 5. Epidemiology research and epigenetics: Translational epidemiology of schizophrenia.-  6. Environmental studies as a tool for detecting epigenetic mechanisms in schizophrenia.- 7. Imprinting, inactivation and the behavioural genetics of the X-chromosome.-  8. The strategies of the genes: genomic conflicts, attachment theory and  development of the social brain -- 9. Genomic imprinting effects on brain and behavior; future directions -- 10. Epigenetic influence of the social environment -- 11. Towards an understanding of the dynamic inter-dependence of genes and environment in the regulation of phenotype.  Nurturing our epigenetic nature.- 12. Histone deacetylase inhibitors: a novel therapeutic approach for cognitive disorders.-  13. Epigenetic mechanisms of memory consolidation.-  14. Epigenetic mechanisms in memory formation -- Sub
Title from title screen (viewed October 9, 2023)
Electronic reproduction
Keywords: Genetic regulation; Brain; Epigenesis